2019
DOI: 10.1590/0001-3765201920180907
|View full text |Cite
|
Sign up to set email alerts
|

Response of duck breeders to dietary L-Carnitine supplementation during summer season

Abstract: A total number of 300 (225 ducks and 75 drakes) Sudani ducks, 28-wk-old were divided into five groups to investigate the effects of dietary L-carnitine (LC) supplementation on productive, hatching and physiological performance as well as nutrients digestibility coefficients. The results indicated that the productive performance and Semen quality parameters (ejaculate volume, sperms concentration and advanced motility) were significantly improved by LC supplementation (150-450 mg /kg diet) as compared to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In the present study, increasing Lys‐Met above NRC recommendations with or without L‐carnitine improved feed efficiency, but L‐carnitine or Lys‐Met alone had no effects on feed utilization and egg production. These results partially agreed with those obtained by El‐kelawy, 2017 ; Rizk et al., 2019 ; Sigolo et al., 2019 . In a previous study, Leibetseder ( 1995 ) also found no effect of dietary L‐carnitine (500 mg/kg) on laying performance of broiler breeders.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, increasing Lys‐Met above NRC recommendations with or without L‐carnitine improved feed efficiency, but L‐carnitine or Lys‐Met alone had no effects on feed utilization and egg production. These results partially agreed with those obtained by El‐kelawy, 2017 ; Rizk et al., 2019 ; Sigolo et al., 2019 . In a previous study, Leibetseder ( 1995 ) also found no effect of dietary L‐carnitine (500 mg/kg) on laying performance of broiler breeders.…”
Section: Discussionsupporting
confidence: 91%
“…Sperm membrane integrity may be altered by oxidative stress, leading to reduced motility and integrity of acrosome, increased DNA degeneration and low fertility of males (Najafi et al, 2019). Under high ambient temperature conditions, treatment with exogenous antioxidants is considered as an alternative strategy for blocking the deleterious effects of oxidative damage on the quality of fresh semen and male fertility (Del Prete et al, 2018; Rizk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is also well-known as a fat-burning agent, but it is rarely used in animal husbandry ( 40 ). It has been reported in the literature that the addition of L-carnitine to the summer diet improves the growth performance of ducks ( 41 ). Notably, L-carnitine significantly improved nutrient digestibility coefficients in ducks.…”
Section: Discussionmentioning
confidence: 99%